In-Situ Laboratory for CO2 controlled-release experiments and monitoring in a fault zone in Western Australia. Issue 1 (1st December 2019) - Michael, Karsten; Avijegon, Arsham; Ricard*,, Ludovic; Myers, Matt; Tertyshnikov, Konstantin; Pevzner, Roman; Strand, Julian; Freifeld, Barry; Woitt, Mark; Pervukhina, Marina; Feitz, Andrew; Pejcic, Bobby; et al.
Summary: The In-Situ Laboratory Project (In-situ Lab) entails a configuration of wells at approximately 400 m depth for monitoring the controlled release of CO2 in a fault zone at the South West Hub CCS Flagship project in Western Australia. The project aims to evaluate the ability to monitor and detect unwanted leakage of CO2 from a storage complex. The In-Situ Lab consists of three instrumented wells up to 400 m deep: 1) Harvey-2 – primarily for CO2 injection, 2) a fiberglass geophysical monitoring well with behind-casing instrumentation, and 3) a shallow groundwater well for fluid sampling. A controlled- release test involving the injection of 38 tonnes of CO2 between 336-342 m depth was conducted successfully in February 2019. Monitoring during the CO2 controlled-release test included: a) continuous downhole pressure and temperature recording in the injection well, b) recording of pressure and temperature at the wellhead and at various points in the injection system, c) regular distributed temperature measurements, d) multiple vertical seismic profiling surveys using the behind-casing distributed acoustic sensor fiber-optic cable and geophones, e) electric resistivity imaging, f) groundwater sampling, g) comprehensive soil flux and atmospheric monitoring surveys, h) collection of gas samples from the surface injection facilities, i) recording of passive seismic data close to the injection well and in the wider area around the well lease, j) downhole video camera surveys, and k) pulsed neutron and induction logging. The In-Situ Lab has the potential to form an enduring research facility at the South West Hub to enable further research of the characterisation of CO2 migration in fault zones and the shallow groundwater environment.